Disentangling Jihad, Political Violence and Media - Dörre (Edinburgh University Press, 2023)
Explores how Jihad, political violence and audio-visual media are entangled in particular ways as discursive formationsFosters critical perspectives on the invocation of a narrow understanding of jihad and political violence in different social contextsPoints to the operation of media and aesthetic means to articulate or defy notions of jihad in the context of political violenceComprises 16 case studies on forms of knowledge production, aesthetic manifestations, socio-political enactments, and archival practices that shape the entanglement of jihad, political violence, and mediaPresents empirically-grounded research from the perspective of Anthropology, Art History, Cultural Studies, Islamic Studies, Media Studies, and Political ScienceAdvances reflections on knowledge production and ethical challenges of research in this fieldThe entanglement of Jihad, Political Violence, and Media has determined the lives of Muslims in Europe and the US over the past 20 years. This book unravels the nexus of these elements, to critically examine how their conjunction is perpetuated, reproduced, or disputed. In 16 case studies, the contributors critically reflect on the identification of jihad with political violence, address the academic, legal, political and broader public production of knowledge on this topic, examine the aesthetic formations involved in the mediation and reaffirmation of this narrow understanding, explore the experiential worlds of people whose ideas and actions are labelled as and affected by notions of violent jihad, and illuminate the institutional and media contexts (e.g. of archives) in which an entanglement of jihad and political violence takes effect, with profound consequences.This volume decentres dominant discourses on so-called jihadist actors and deradicalization contexts to offer more nuanced understandings of the political and socio-cultural contexts